2013
DOI: 10.4067/s0718-27242013000400003
|View full text |Cite
|
Sign up to set email alerts
|

Customer Integration in Service Innovation: An Exploratory Study

Abstract: Prominent industry projects, as well as an extensive literature suggest the importance of customer integration for companies' innovation success. This appears to be especially true for service firms, which inherently build on customer interaction. Despite this appreciation of the approach, there are comparably few empirical analyses of the positive and negative effects of customer integration. In this exploratory study, we build on established customer role concepts to study the status quo of customer integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Externally, factors studied so far include customer involvement in service innovation, stakeholder relationships and support, and coordination between the firm and its partners [15][16][17]. For instance, Geum et al found that the provision of suppliers' support using their valuable knowledge and technology contributes to the service innovation of the firm [18]; Straub et al argued that the participation of customers, acting as a service-specifier and quality-controller in the innovation process, is crucial to the success of service innovation [19]; and Rusanen et al claimed that network capability positively affects the performance of service innovation by improving the effectiveness of relationship learning [20].…”
Section: Introductionmentioning
confidence: 99%
“…Externally, factors studied so far include customer involvement in service innovation, stakeholder relationships and support, and coordination between the firm and its partners [15][16][17]. For instance, Geum et al found that the provision of suppliers' support using their valuable knowledge and technology contributes to the service innovation of the firm [18]; Straub et al argued that the participation of customers, acting as a service-specifier and quality-controller in the innovation process, is crucial to the success of service innovation [19]; and Rusanen et al claimed that network capability positively affects the performance of service innovation by improving the effectiveness of relationship learning [20].…”
Section: Introductionmentioning
confidence: 99%
“…Service innovation, a concept that has long been studied in service management research, is a part of the basis for different issues in the service industry such as customerinvolvement (Bendapudi and Leone 2003), knowledge transformation (Muller and Zenker 2001), cooperation (Mention 2011), innovation patterns (Chang et al 2012), and servicespecific measurement (Hipp and Grupp 2005). Beyond the service industry, researchers have recently begun to examine the high-tech industry within the contexts of co-production (Chen et al 2011), small-and-medium enterprises (SMEs) (Amara et al 2008), knowledge acquisition (Cassiman and Veugelers, 2006), and customer integration (Straub et al 2013). Service innovation was first discussed by Vandermerwe and Rada (1989), who refer the process of creating value by adding services to product offering.…”
Section: Introductionmentioning
confidence: 99%